SOME OPINIONS ABOUT “SAODAT ASRI QISSALARI” - Samadova Dilnoza (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
In this article,there is talk about the life attitudes of our Prophet(pbuh),the characteristics of his behavior,and the priceless quatilies given to him.In addition,about his enthusiasm in learning Islam to people and in the way of following them.